DNA methylation in systemic lupus erythematosus. (April 2017) - Hedrich, Christian M; Mäbert, Katrin; Rauen, Thomas; Tsokos, George C
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease facilitated by aberrant immune responses directed against cells and tissues, resulting in inflammation and organ damage. In the majority of patients, genetic predisposition is accompanied by additional factors conferring disease expression. While the exact molecular mechanisms remain elusive, epigenetic alterations in immune cells have been demonstrated to play a key role in disease pathogenesis through the dysregulation of gene expression. Since epigenetic marks are dynamic, allowing cells and tissues to differentiate and adjust, they can be influenced by environmental factors and also be targeted in therapeutic interventions. Here, we summarize reports on DNA methylation patterns in SLE, underlying molecular defects and their effect on immune cell function. We discuss the potential of DNA methylation as biomarker or therapeutic target in SLE.